Effect of WO3 Nanoparticles Morphology on the Catalytic Properties. (2016) - Dirany, N.; Arab, M.; Leroux, Ch.; Villain, S.; Madigou, V.; Gavarri, J.R.
Abstract: Tungsten trioxide WO3 powder have been synthesized at room temperature with aqueous mineralization processes, with two distinct morphologies: nanoplates and pseudospheres. The aim of this work is tohighlight the influence of the nanoparticles morphology on the carbon monoxide CO catalytic gaseous transformation and photocatalytic decomposition of Rhodamine in aqueous medium. The samples were characterized by X-ray diffraction, scanning and transmission electron. The nanoplates of WO3 show significantly higher photocatalytic activity than the pseudospheres, due to the large surface area. The CO oxidation was performed under air and the conversion reaction is not complete leaving residual CO and without shape effect.